Cross-sectional and longitudinal interaction effects of physical activity and APOE-ε4 on white matter integrity in older adults: The MAPT study. (October 2021) - Raffin, Jérémy; Rolland, Yves; He, Lingxiao; Perus, Lisa; Mangin, Jean-François; Gabelle, Audrey; Virecoulon Giudici, Kelly; Vellas, Bruno; de Souto Barreto, Philipe
Highlights: APOE-ε4 status moderated the association between level of physical activity and white matter integrity. Physical activity was associated with white matter integrity in APOE-ε4 carriers but not in non-carriers. In APOE-ε4 carriers, light physical activity but not moderate to vigorous or total physical activity was associated with white matter integrity. Higher levels of light physical activity were associated with higher axial and mean diffusivity values over time. We hypothesize that light physical activity protects against fiber loss in tracts containing crossing fibers. ABSTRACT 1 : Background: Physical activity (PA) has been shown to modulate the detrimental effect of carrying the apolipoprotein-E epsilon 4 ( APOE-ɛ4 ) allele on brain structure. However, the current literature mainly provides cross-sectional data, and longitudinal studies investigating the interaction between genotype and PA on white matter (WM) integrity are lacking. Objectives: We investigated both the cross-sectional and the longitudinal interactive effects of APOE-ɛ4 and PA on WM integrity in older adults. Methods: Fractional anisotropy, as well as axial, radial, and mean diffusivity, extracted from brain diffusion tensor imaging (DTI) were used to assess WM integrity in non-demented older adults. They were categorized according to their APOE-ɛ4 status (carriers vs. non-carriers), and their level of total (TPA), moderate to vigorous (MVPA) and light (LPA) PA were assessed using a questionnaire. Mixed model regressions were performed to test the interactive effects of APOE-ɛ4 status and PA on WM integrity at baseline and over a 3-year follow-up. Results: 190 subjects with a mean age 74.5 years (SD = 3.9) were examined. Despite a lack of cross-sectional associations, sensitivity analyses revealed that, in the carrier group only, higher levels of LPA, but not MVPA, were mainly associated with higher axial and mean diffusivity values over time. Conclusions: This study partially confirms the previously reported interactive associations between PA, APOE-ɛ4 genotype and WM integrity, supporting the hypothesis that PA may protect against fiber loss in WM tracts containing crossing fibers. Future studies assessing sedentary behaviors in addition to PA could bring relevant contributions to the field. Clinical trial registration number from ClinicalTrials.gov: NCT00672685